Individualised Homoeopathic Medicine Resolved Multiple Recalcitrant Verruca Vulgaris: An Evidence-Based Case Report - Purkait, Rajib; Banerjee, Abhiram; Choubey, Gurudev (Homœopathic Links, 2023)
Background Verruca vulgaris commonly known as warts are characterised by common, benign, localised epidermal lesions caused by human papilloma viruses. Various treatment options are available but many of them are invasive and destructive, which may cause damage to the epidermis or discomfort to the patient.Objective The main objective of this case report is to produce pieces of evidence systematically, favouring homoeopathy.Method This is a reported case of verruca vulgaris, presented with multiple rough, itchy, cauliflowers like warty growth on the dorsal aspect of both the feet. Outcome Related to Impact on Daily Living (ORIDL) scale was used as a patient-reported outcome measure for subjective assessment. Dermatology Life Quality Index (DLQI) questionnaire was used to assess the improvement in the quality of life. Photographs were taken as objective evidence. Lastly, possible causal attributions were evaluated by using Modified Naranjo Criteria for Homeopathy (MONARCH).Result The case was improved on the ORIDL scale (score +4). Quality of life was improved (score 10 to 0) and documented through the DLQI questionnaire. Photographs were presented as objective evidence. The high total score (+9) of MONARCH established the possible causal attributions between the homoeopathic intervention and clinical improvement in the patient.Conclusion In this case, individualised homoeopathic medicine, Thuja occidentalis, is proved to be effective in the resolution of all warts within a plausible time frame of medicine intake. Further documentation and studies are warranted in the future.
Keywords: Homoeopathy; Thuja occidentalis; Verruca vulgaris; Case Report; ORIDL; MONARCH